The role of the corpus callosum and extra striate visual areas in stereoacuity in macaque monkeys. - Cowey, A; Wilkinson, F (1991)
Stereoacuity was measured in six normal male rhesus monkeys by requiring them to indicate the closer of two vertical line targets. Their stereoacuity ranged from 13-23 arc sec and was as good as that of human observers tested in the same way. Sectioning the splenium of the corpus callosum, either before or after removing the foveal representation in visual area 2, had no effect on stereoacuity thresholds, indicating that the splenium is not essential for the detection of small retinal disparities at the visual mid-line. In contrast, removal of the foveal representation in V2 permanently and markedly elevated stereoacuity thresholds, almost to the level observed in two monkeys after removal of the representation in striate cortex of the central 5 degrees of the retina. Posterior infero-temporal ablation also impaired stereoacuity, though less strikingly. In these two monkeys, the effect of subsequent damage to the rostral superior colliculi was examined. One animal was unimpaired. In the other, in which the pre-tectum was damaged, the stereoacuity threshold was substantially raised, most plausibly as a consequence of imperfect binocular fixation.